Ars 95 Helsinki. - Ars 95 Helsinki (Helsinki : The Museum of Contemporary Art, 1995)
Acconci, Vito ; Applebroog, Ida ; Balka, Miroslaw ; Baltz, Lewis ; Barney, Matthew ; Beriou ; Bjorlo, Per Inge ; Bloom, Barbara ; Bourgeois, Louise ; Cadieux, Geneviève ; Chadwick, Helen ; Coplans, John ; Deacon, Richard ; Delvoye, Wim ; Dumas, Marlene ; Endo, toshikatsu ; Fabro, Luciano ; Gec, Stefan ; Gelzis, Kristaps ; Gober, Robert ; Gonzaez-Torres, Felix ; Gormley, Antony ; Graham, Dan ; Gröting, Asta ; Hatoum, Mona ; Hákon, Hulda ; Heiskanen, Outi ; Hill, Gary ; Troy Innocent ; Jaar, Alfredo ; Jammes, Louis ; Kapoor, Anish ; Kawaguchi, Yoichiro ; Kelley, Mike ; Komar & Melamid ; Kuprianov & Fishkin ; Kusama, Yayoi ; Lafontaine, Marie-Jo ; Lasker, Jonathan ; Latham, William ; Leccia, Ange ; Lucas, Sarah ; Löfdahl, Eva ; Marden, Brice ; Miller, Brad ; Rand & Robyn Miller ; de Monchaux, Cathy ; Muñoz, Juan ; Munson, Portia ; Muntadas, Antonio ; Männikkö, Esko ; Nauman, Bruce ; Niskanen, Pekka ; Niva, Jussi ; Obata, Masayoshi ; Odenbach, Marcel ; Oursler, Tony ; Pétursson, Finnbogi ; Piper, Adrian ; Plenge Jakobsen, Henrik ; Polke, Sigmar ; Raetz, Markus ; Ray, Charles ; Richter, Gerhard ; Rollof, Ulf ; Roos, Nina ; Schäfer, Rudolf ; Serrano, Andres ; Shono, Haruhiko ; Sims, Karl ; Sugimoto, Hiroshi ; Taaffe, Philip ; Tamblyn, Christine ; Toomik, Jaan ; Trockel, Rosemarie ; Tuymans, Luc ; Urbonas, Gediminas ; Uutinen, Marianna ; Vaisman, Meyer ; Weiner, Lawrence ; Whiteread, Rachel ; Willats, Stephen ; VNS ; Matrix ; Wodiczko, Krzysztof
Ars 95 Helsinki, The Museum of Contemporary Art, Helsinki, 11.2. - 28.5.1995
boek